THE EFFECT OF SWITCHING BARRIER ON REPURCHASE INTENTION : (STUDY ON FEB UNM STUDENTS WHO USE GSM IM3 OOREDOO PREPAID) - Putri, Zaskiyah Ameliah; Musa, Muh. Ichwan; Haeruddin, Muh. Ilham Wardhana; Hasbiah, Siti; Aswar, Nurul Fadilah (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to determine the effect of switching costs, attractiveness of alternatives, and interpersonal relationships on repurchase intention (study on FEB UNM students who use IM3 Ooredoo Prepaid GSM). This research is quantitative research. The population in this study are all active students of FEB UNM Class of 2020 who use prepaid GSM IM3 Ooredoo, using the Sampling method obtained a sample of 100 respondents. The data collection technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) v. 23. The results of this study indicate that switching cost (X1) partially has a positive and significant effect on the repurchase intention of Prepaid GSM IM3 Ooredoo users. Attractiveness of alternative (X2) partially has a positive and significant effect on the repurchase intention of Prepaid GSM IM3 Ooredoo users. Interpersonal Relationship (X3) partially has a positive and significant effect on the repurchase intention of Prepaid GSM IM3 Ooredoo users. As well as switching costs (X1), attractiveness of alternatives (X2), and interpersonal relationships (X3) simultaneously have a positive and significant effect on the repurchase intention of Prepaid GSM IM3 Ooredoo users